Optimal operation of an ice-tank for a supermarket refrigeration system. (February 2022) - Brok, Niclas; Green, Torben; Heerup, Christian; Oren, Shmuel S.; Madsen, Henrik
Abstract: The increasing proportion of renewable energy sources in power grids leads to challenges concerning balancing production and consumption. One solution to this grid challenge is to utilize demand-side flexibility. To use the full potential of demand-side flexibility, dynamical models and optimal control methods must be used. This paper demonstrates how demand-side flexibility can be enabled for a refrigeration system using an add-on ice-tank module to actively curtail the refrigeration system and thereby leveraging time-varying power prices. The operation of the ice-tank is the solution to an optimal control problem that minimize the integrated electricity costs. This optimal control problem is solved numerically and the performance of the strategy is successfully tested in a real experiment where cost-savings of approximately 20% are observed (compared to not having an ice-tank available). The proposed optimal control strategy is tested in real-life experiments spanning over 24 h. The dynamical relation between the operation of the ice-tank and the power consumption (the compressor capacity) is modelled using stochastic differential equations. This differential equation model is calibrated on 13 h of training data using the continuous–discrete Kalman filter and the maximum likelihood framework.